Changes in contractility determine coronary haemodynamics in dyssynchronous left ventricular heart failure, not vice versa. (June 2018) - Claridge, Simon; Briceno, Natalia; Chen, Zhong; De Silva, Kalpa; Modi, Bhavik; Jackson, Tom; Behar, Jonathan M.; Niederer, Steven; Rinaldi, Christopher A.; Perera, Divaka
Abstract: Background: Biventricular pacing has been shown to increase both cardiac contractility and coronary flow acutely but the causal relationship is unclear. We hypothesised that changes in coronary flow are secondary to changes in cardiac contractility. We sought to examine this relationship by modulating coronary flow and cardiac contractility. Methods: Contractility and lusitropy were altered by varying the location of pacing in 8 patients. Coronary autoregulation was transiently disabled with intracoronary adenosine. Simultaneous coronary flow velocity, coronary pressure and left ventricular pressure data were measured in the different pacing settings with and without hyperaemia and wave intensity analysis performed. Results: Multisite pacing was effective at altering left ventricular contractility and lusitropy (pos. dp/dtmax −13% to +10% and neg. dp/dtmax −15% to +17% compared to baseline). Intracoronary adenosine decreased microvascular resistance (362.5 mm Hg/s/m to 156.7 mm Hg/s/m, p < 0.001) and increased LAD flow velocity (22 cm/s vs 45 cm/s, p < 0.001) but did not acutely change contractility or lusitropy. The magnitude of the dominant accelerating wave, the Backward Expansion Wave, was proportional to the degree of contractility as well as lusitropy (r = 0.47, p < 0.01 and r = −0.50, p < 0.01). Perfusion efficiency (the proportion of accelerating waves) increased at hyperaemia (76% rest vs 81% hyperaemia, p = 0.04). Perfusion efficiency correlated with contractility and lusitropy at rest (r = 0.43 & −0.50 respectively, p = 0.01) and hyperaemia (r = 0.59 & −0.6, p < 0.01). Conclusions: Acutely increasing coronary flow with adenosine in patients with systolic heart failure does not increase contractility. Changes in coronary flow with biventricular pacing are likely to be a consequence of enhanced cardiac contractility from resynchronization and not vice versa.